Речеведение: в поисках теории - ШМЕЛЕВА, ТАТЬЯНА В. (Stylistyka, 2021)
Тhе article represents an attempt to make up а theory of speech based оп the notion that its main parameters are role, texture, sphere, janre and rule. Тhе study of each of the above mentonend features can coustitute а separate section of speechology, characterized in terms of the degree of knowledge of the subject and the prospect of study speechology is belived to Ье а theoretical basis for speech culture and an important discipline of modern philology.